Defining Genetic Privacy in the Context of Sports Genetic Testing in athletes - Xi Li, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2023)
The safeguarding of genetic information is essential, particularly within the domain of sports genetics testing. This research delves into the nuanced definition of genetic privacy under the backdrop of genetic testing in sports. While many scholars regard genetic information as an inherent component of the right to privacy, it is crucial to recognize that not all genetic information falls squarely within the realm of privacy. Due to the distinctive nature of genetic data, only specific segments can be considered under the umbrella of privacy rights. Additionally, genetic information that pertains to family or group dynamics transcends the boundaries of individual privacy rights. In cases where genetic information is shared among multiple parties, the owners do not possess unilateral control over these shared genetic segments. As a novel facet of privacy rights, gene privacy introduces unique dimensions that differ from conventional privacy rights. It encompasses the fifth right—the right not to know specific genetic information. To establish a robust framework for judicial protection of genetic privacy, it is imperative to undertake comprehensive research on the right to genetic information privacy. Such research forms the bedrock upon which a scientifically informed path to judicial protection of genetic privacy in the sports context can be developed.